KEPUASAN PELANGGAN RUMAH SAKIT, SURVEI DI RSU MARTHA FRISKA MULTATULI MEDAN TAHUN 2017 - Tischa Rahayu Fonna (LP2MTBM MAKARIOZ, 2018)
Hospitals have various types of health services that can be seeded to maintain patient loyalty. One type of health services in hospitals is inpatient services, inpatient services are a major concern of hospital management. The increasingly fierce competition has recently demanded a service provider institution to always pamper customers by providing the best service. Customers will look for products in the form of goods or services from companies that can provide the best service to them. The researcher will find out about the quality of services that have been provided to inpatients at Martha Friska Multatuli General Hospital in Medan. Because what is related to the patient's perception of the quality of service with the level of patient satisfaction, especially for patients hospitalized at the Martha Friska Multatuli General Hospital in Medan is very important to improve better service